Éduquer les éducateurs : les revues pédagogiques égyptiennes de l’entre-deux-guerres - Iman Farag (Revue des Mondes Musulmans et de la Méditerranée)
This contribution is based on three pedagogical journals associated with different groups of teachers in Egypt during the interwar period. The Sahîfat al-Mu talli-mîn (1923-1925), published by the Teachers' Union may be situated within the professional reorganisation characteristic of that time. Teachers are both authors and readers of this journal which illustrates a unitary ephemeral movement. Sahîfat al-ta'lîm al-ilzâmî (1933-1935) was published by elementary school teachers who taught in the free schools established in 1905 and which were socially looked down upon. The publication of this journal appears within the framework of a collective mobilisation for obligatory and elementary school education. The Majallat al-tarbiya al-hadîtha (1927-1951), published by the American University of Cairo, illustrates the voluntary transfer of knowledge towards Egyptian teachers who are being inculcated with American pedagogy.